ANALYSIS OF STUDENT'S CRITICAL THINKING ABILITY IN SOLVING HOTS (HIGHER-ORDER THINKING SKILLS) PROBLEMS WITH CREATIVE PROBLEM-SOLVING MODEL - Yunis Setiyowati; Ali Shodikin (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
This study aims to determine students' critical thinking skills in solving HOTS (Higher order thinking skills) questions with creative problem-solving models. This research is a descriptive study using a qualitative approach. The subjects of this study were 4 students of class VIII A of the State Junior High School 1 Lamongan for the academic year 2021/2022. Taking the subject is based on the result of a description test consisting of two questions. The data used are the results of the test and what will happen in the interview recording. The instrument in this study was a description test consisting of two questions. The data used in this study were tests and interview recordings. according to the data analysis that has been done, the results of this study show that: The higher the Creative Problem Solving students, the students' critical thinking skills in solving HOTS (Higher order thinking skills) questions are also getting better, and vice versa if the students' Creative Problem Solving is lower then Students' critical thinking skills in solving HOTS (Higher order thinking skills) questions are also not good